Paths toward the nation: Islam, community, and early nationalist mobilization in Eritrea, 1941-1961 - Venosa, Joseph L. (Ohio University research in international studies. Africa series, 2014)
In the early and mid-1940s, during the period of British wartime occupation, community and religious leaders in the former Italian colony of Eritrea engaged in a course of intellectual and political debate that marked the beginnings of a genuine national consciousness across the region. During the late 1940s and 1950s, the scope of these concerns slowly expanded as the nascent nationalist movement brought together Muslim activists with the increasingly disaffected community of Eritrean Christians. The Eritrean Muslim League emerged as the first genuine proindependence organization in the cou